Graduate Students Critical Thinking on Their Analytical Paper - Sudirman N; Ratna Dewi; Syamsiarna Nappu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The research aimed to find out the ability of the graduate student in writing analytical papers and to find out critical thinking which expressed graduate student on their analytical paper. The ability of graduate student has in writing analytical papers refer to Whitakers’ pattern (2009). The critical thinking is express by graduate students on their analytical paper refers to Factions’ The Holistic Critical Thinking Scoring Rubric. This research used a Descriptive Quantitative Method. The sample of this research was graduate students’ thesis from the Graduate Program of English Language Education at Muhammadiyah University of Makassar at second semester of 2022 – 2023 academic years. The total was 14 master's theses. The total sample was fourteen graduate students’ papers. The procedure of this research was collected by analyzing the graduate students’ papers by using a rubric. The results of research found that 1) the ability graduate student have in writing analytical papers was good which the students wrote   hook, bridge and thesis in introduction. Topic sentences are clear and some connection to the thesis, the supporting consistently develops the main idea, and transitions show connection between ideas. There are restate thesis and summarized in conclusion. 2) The critical thinking is express by graduate student in their analytical which identified based on the Facione’ The Holistic Critical Thinking Scoring Rubric which focuses on six cognitive abilities (interpretation, analysis, inference, evaluation, explanation and self-regulation).